Carbon-ion radiotherapy for locally recurrent rectal cancer: Japan Carbon-ion Radiation Oncology Study Group (J-CROS) Study 1404 Rectum. (March 2019) - Shinoto, Makoto; Yamada, Shigeru; Okamoto, Masahiko; Shioyama, Yoshiyuki; Ohno, Tatsuya; Nakano, Takashi; Nemoto, Kenji; Isozaki, Yuka; Kawashiro, Shohei; Tsuji, Hiroshi; Kamada, Tadashi
Highlights: We analyzed 224 LRRC patients treated with C-ion RT at three institutions. The median follow-up period from the initiation of C-ion RT was 62 months. The OS rates were 73% at 3 years and 51% at 5 years. Grade 3 acute ( n  = 3) and grade 3 late ( n  = 12) toxicity was observed. C-ion RT for LRRC showed relatively favorable outcomes and limited toxicity. Abstract: Purpose: We investigated the efficacy and safety of carbon-ion radiotherapy (C-ion RT) for locally recurrent rectal cancer (LRRC). Patients and methods: Data from patients with LRRC treated with C-ion RT from November 2003 to December 2014 at three institutions were retrospectively analyzed. The endpoints of this clinical trial were overall survival (OS), local control (LC), and acute/late toxicity. Results: A total of 224 patients' data were collected. The prescribed dose was 70.4 Gy (relative biological effectiveness [RBE]-weighted absorbed dose) or 73.6 Gy (RBE) in 16 fractions. The median follow-up period from the initiation of C-ion RT was 62 months (range 6–169 months). The OS rates were 73% (95% confidence interval [CI], 67%–79%) at 3 years and 51% (95%CI 44%–58%) at 5 years. The LC rates were 93% (95%CI 88%–96%) at 3 years, and 88% (95%CI 82%–93%) at 5 years. Grade 3 acute toxicity was observed in three patients: gastrointestinal toxicity ( n  = 1) and pelvic infection ( n  = 2). Grade 3 late toxicity was observed in 12 patients: skin reaction ( n  = 2), gastrointestinal toxicity ( n  = 2), neuropathy ( n  = 1), and pelvic infection ( n  = 7). There was no grade 4 or 5 acute or late toxicity. Conclusions: This first multi-institutional analysis of C-ion RT for LRRC indicated relatively favorable outcomes with limited toxicities.